Rice Brittle Culm19 Encoding Cellulose Synthase Subunit CESA4 Causes Dominant Brittle Phenotype But has No Distinct Influence on Growth and Grain Yield - Xiaozhi Ma (SpringerOpen, 2021)
Abstract Background Mechanical strength is a crucial agronomic trait in rice (Oryza sativa), and brittle mutants are thought suitable materials to investigate the mechanism of cell wall formation. So far, almost all brittle mutants are recessive, and most of them are defected in multiple morphologies and/or grain yield, limiting their application in hybrid breeding and in rice straw recycling. Results We identified a semi-dominant brittle mutant Brittle culm19 (Bc19) isolated from the japonica variety Nipponbare through chemical mutagenesis. The mutant showed the same apparent morphologies and grain yield to the wild type plant except for its weak mechanical strength. Its development of secondary cell wall in sclerenchyma cells was affected, along with reduced contents of cellulose, hemicellulose, lignin and sugars in culms and leaves. Positional cloning suggested that the Bc19 gene was allelic to OsCESA4, encoding one of the cellulose synthase A (CESA) catalytic subunits. In this mutant, a C-to-T substitution occurred in the coding sequence of BC19, causing the P507S missense mutation in its encoded product, which was located in the second cytoplasmic region of the OsCESA4 protein. Furthermore, introducing mutant gene Bc19 into the wild-type plant resulted in brittle plants, confirming that the P507S point mutation in OsCESA4 protein was responsible for the semi-dominant brittle phenotype of Bc19 mutant. Reverse correlation was revealed between cellulose contents and expression levels of mutant gene Bc19 among the homozygous mutant, the hybrid F1 plant, and the Bc19 overexpression transgenic plants, implying that gene Bc19 might affect cellulose synthesis in a dosage-dependent manner. Conclusions Bc19, a semi-dominant brittle mutant allele of gene OsCESA4, was identified using map-based cloning approach. The mutated protein of Bc19 possessing the P507S missense mutation behaved in a dosage-dependent semi-dominant manner. Unique brittle effect on phenotype and semi-dominant genetic quality of gene Bc19 indicated its potential application in grain-straw dual-purpose hybrid rice breeding.